Determination of Total Flavonoid Content of Ashitaba (Angelica keiskei Koidz.) Leaf Extract Using UV-Vis Spectrophotometry - Andriani, Baiq Yunita; Rahayu, Supiani; Rahayu, Lale Budi Hutami (THRIVE Health Science Journal, 2026)
Ashitaba (Angelica keiskei Koidz.) is a medicinal plant known to be rich in active flavonoid compounds, particularly chalcones, which exhibit antioxidant, anti-inflammatory, and antidiabetic activities. This study aimed to determine the total flavonoid content in Ashitaba leaf extract obtained from Sembalun Village using UV-Vis spectrophotometry. The extract was obtained by maceration using 96% ethanol. Quantitative analysis was performed at the maximum wavelength of 415 nm, with quercetin as the standard. Calibration curves were prepared using quercetin concentrations of 20, 30, 40, 50, and 60 ppm on the X-axis, with absorbance values of 0.297, 0.337, 0.436, 0.509, and 0.588 on the Y-axis, resulting in the regression equation Y = 0.0094x + 0.0472 with a correlation coefficient (r) of 0.9677, indicating a linear relationship between concentration and absorbance. Absorbance values of the sample measured in triplicate were 0.661, 0.634, and 0.676, yielding an average total flavonoid content of 25.948 mgQE/g in Ashitaba leaf extract.